Bone marrow‐derived mesenchymal stem cells promote invasiveness and transendothelial migration of osteosarcoma cells via a mesenchymal to amoeboid transition. Issue 5 (31st March 2018) - Pietrovito, Laura; Leo, Angela; Gori, Valentina; Lulli, Matteo; Parri, Matteo; Becherucci, Valentina; Piccini, Luisa; Bambi, Franco; Taddei, Maria Letizia; Chiarugi, Paola
Abstract : There is growing evidence to suggest that bone marrow‐derived mesenchymal stem cells (BM‐MSCs) are key players in tumour stroma. Here, we investigated the cross‐talk between BM‐MSCs and osteosarcoma (OS) cells. We revealed a strong tropism of BM‐MSCs towards these tumour cells and identified monocyte chemoattractant protein (MCP)‐1, growth‐regulated oncogene (GRO)‐α and transforming growth factor (TGF)‐β1 as pivotal factors for BM‐MSC chemotaxis. Once in contact with OS cells, BM‐MSCs trans‐differentiate into cancer‐associated fibroblasts, further increasing MCP‐1, GRO‐α, interleukin (IL)‐6 and IL‐8 levels in the tumour microenvironment. These cytokines promote mesenchymal to amoeboid transition (MAT), driven by activation of the small GTPase RhoA, in OS cells, as illustrated by the in vitro assay and live imaging. The outcome is a significant increase of aggressiveness in OS cells in terms of motility, invasiveness and transendothelial migration. In keeping with their enhanced transendothelial migration abilities, OS cells stimulated by BM‐MSCs also sustain migration, invasion and formation of the in vitro capillary network of endothelial cells. Thus, BM‐MSC recruitment to the OS site and the consequent cytokine‐induced MAT are crucial events in OS malignancy. Abstract : Evidence suggests bone marrow‐derived mesenchymal stem cells (BM‐MSCs) are key players in tumor stroma. We investigated cross‐talk between BM‐MSCs and osteosarcoma (OS) cells. Upon contact with OS cells BM‐MSCs transdifferentiate into cancer‐associated fibroblasts, increasing pivotal chemotaxis factors MCP‐1, GRO‐α, IL‐6 and IL‐8 levels in the tumor microenvironment. This promotes GTPase RhoA driven mesenchymal to amoeboid transition (MAT) resulting in increased aggressiveness in OS cells in terms of motility, invasiveness, and transendothelial migration. BM‐MSCs recruitment and the consequent cytokine‐induced MAT are crucial events in OS malignancy.